Representation and Spatial Analysis in Geographic Information Systems. - Miller, Harvey J.; Wentz, Elizabeth A. (Annals of the Association of American Geographers, 2003)
A review of geographic representations, associated analytical possibilities, and relevant computational tools in geographic information systems (GIS) Science and combined spatial analysis literatures is presented. Research and development frontiers relating to GIS are explored.